If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (4u + -6)(4 + u) = 0 Reorder the terms: (-6 + 4u)(4 + u) = 0 Multiply (-6 + 4u) * (4 + u) (-6(4 + u) + 4u * (4 + u)) = 0 ((4 * -6 + u * -6) + 4u * (4 + u)) = 0 ((-24 + -6u) + 4u * (4 + u)) = 0 (-24 + -6u + (4 * 4u + u * 4u)) = 0 (-24 + -6u + (16u + 4u2)) = 0 Combine like terms: -6u + 16u = 10u (-24 + 10u + 4u2) = 0 Solving -24 + 10u + 4u2 = 0 Solving for variable 'u'. Factor out the Greatest Common Factor (GCF), '2'. 2(-12 + 5u + 2u2) = 0 Factor a trinomial. 2((-4 + -1u)(3 + -2u)) = 0 Ignore the factor 2.Subproblem 1
Set the factor '(-4 + -1u)' equal to zero and attempt to solve: Simplifying -4 + -1u = 0 Solving -4 + -1u = 0 Move all terms containing u to the left, all other terms to the right. Add '4' to each side of the equation. -4 + 4 + -1u = 0 + 4 Combine like terms: -4 + 4 = 0 0 + -1u = 0 + 4 -1u = 0 + 4 Combine like terms: 0 + 4 = 4 -1u = 4 Divide each side by '-1'. u = -4 Simplifying u = -4Subproblem 2
Set the factor '(3 + -2u)' equal to zero and attempt to solve: Simplifying 3 + -2u = 0 Solving 3 + -2u = 0 Move all terms containing u to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + -3 + -2u = 0 + -3 Combine like terms: 3 + -3 = 0 0 + -2u = 0 + -3 -2u = 0 + -3 Combine like terms: 0 + -3 = -3 -2u = -3 Divide each side by '-2'. u = 1.5 Simplifying u = 1.5Solution
u = {-4, 1.5}
| -28=-4/9u | | 3n-n=12 | | 4w(w+2)(w-9)=0 | | (2/5)*j=15 | | (4x+43)/2=32 | | 2/5j=15 | | y^2-8y+16=36 | | 5(x-3)+64=-2x | | 3(6-x)=-5x-7-3x | | (2v+5)(7+v)=0 | | c=a+2b | | -8(c+6)=4(x-6) | | 5x-15.4=15.4(x-3.6) | | 18x^2-27x=-10 | | (6/y)(3y/6) | | 125=0.5x*(10+15) | | -6+18=7-1(4x+9) | | w^2+w-2=0 | | 8(c-4)=-2(c+6) | | -a^2-10a+25=25 | | 4.5(x-4)=-0.5x+22 | | 6(3a+14)=90 | | 0=x^2-32x-5 | | B^2+5b+1= | | 1/2t+3=5 | | (5x/4)+(x+4) | | 10=0.5*2*(6+x) | | 6x+3=9(x-4) | | 8x^2y+12xy^2= | | 6x+3=9x | | 1m-5=3m | | 7/9=y+5 |